THE ROLE OF DIGITAL TALENT ON ACCELERATION OF GROWTH CONVENTIONAL MICRO ENTERPRISE TOWARDS DIGITAL START UP - Rizka Iffa Annisa; Sugeng, Didik; Annafi Syam Maella, Nur (Proceeding of International Conference on Multidisciplinary Research, 2024)
The concept of going digital has become an important focus for future economic development for everyone from micro businesses or MSMEs, large technology companies, to national governments. With face-to-face business systems hampered, the pandemic has brought awareness to the importance of digitalization and developing digital skills for MSMEs throughout the world. The biggest challenge for MSMEs in carrying out transformation is the lack of digital talent that is owned and developed with MSMEs. In fact, the presence of digital talent or what is usually called digital talent is very vital to be able to take advantage of market opportunities through digital communication strategies created in the industrial era 4.0, to accelerate the growth of micro-enterprises that are not yet technologically literate or not yet digital-based, which we call conventional MSMEs, moving towards start-up companies. digital-based or digital start-up. This can also take them out of the crush of increasingly tight competition. The aim of this research is to find out whether the presence of digital talent with their digital skills and online communication strategies has an impact and influences readiness to face digital transformation so that it can accelerate the growth of conventional micro businesses towards digital-based start-ups or digital start-ups. This research was conducted on a group of MSMEs assisted by the village government in the Sidoarjo district, East Java, Indonesia. The results of this research show that the ability of digital talent has an important role and is very influential in the digital transformation process of conventional micro-entrepreneurs so that they are able to accelerate the growth of conventional MSMEs into digital start-ups while simultaneously taking them global with a wider market reach, not only national but also international.